Identifying potential risk genes and pathways for neuropsychiatric and substance use disorders using intermediate molecular mediator information - Gedik, Huseyin; Nguyen, Tan Hoang; Peterson, Roseann E.; Chatzinakos, Christos; Vladimirov, Vladimir I.; Riley, Brien P.; Bacanu, Silviu-Alin (Frontiers in Genetics, 2023)
Neuropsychiatric and substance use disorders (NPSUD) have a complex etiology that includes environmental and polygenic risk factors with significant cross-trait genetic correlations. Genome Wide Association Studies (GWAS) of NPSUD yield numerous association signals. However, for most of these regions, we do not yet have a firm understanding of either the specific risk variants or the effects of these variants. Post-GWAS methods allow researchers to use GWAS summary statistics and functional genomics data to infer the likely molecular mediators (transcript, protein and methylation abundances) for the effect of variants on disorders. One group of post-GWAS approaches is commonly referred to as transcriptome/proteome/methylome wide association studies, which are abbreviated as T/P/MWAS (or collectively as XWAS). Since these approaches use biological mediators, the multiple testing burden is reduced to the number of genes (~20,000) instead of millions GWAS SNPs, which leads to increased signal detection. In this work, our aim is to uncover likely risk genes for NPSUD by performing XWAS analyses in two tissues – blood and brain. First, to identify putative causal risk genes, we performed XWAS using the Summary-data based Mendelian Randomization (SMR), which uses as inputs GWAS summary statistics, reference xQTL data and a reference LD panel. Second, given the large comorbidities among NPSUD and the shared cis-xQTLs between blood and brain, we improved XWAS signal detection in NPSUD underpowered analyses by performing joint concordance analyses between XWAS results i) across the two tissues and ii) across NPSUD. All XWAS signals i) were adjusted for HEIDI (non-causality) p-values and ii) used to test for pathway enrichment. The results suggest that there were widely shared gene/protein signals within the Major Histocompatibility (MHC) region on chromosome 6 (BTN3A2 and C4A) and elsewhere in the genome (FURIN, NEK4, RERE and ZDHHC5). The identification of putative molecular genes and pathways underlying risk may offer new targets for therapeutic development. Our study revealed an enrichment of vitamin D and omega-3 in XWAS signals. So, including vitamin D and omega-3 in treatment plans may prove modest but beneficial effect on patients with bipolar disorder.